Franchising for Global Distribution: A Systematic Review - Nurul Ashykin, Abd Aziz; Mohamad Rohieszan, Ramdan; Khairunnisa, Abdul Aziz; Hasif Rafidee, Hasbollah; Noreen Noor, Abd Aziz; Nik Syuhailah, Nik Hussin; Md Zaki, Muhamad Hasan (Korea Distribution Science Association (KODISA), 2023)
Purpose: The purpose of this study is to explore areas that have been studied extensively in previous studies related to franchising as a platform for global distribution. Furthermore, franchising is a strategic distribution method that gives entrepreneurs the opportunity to replicate an established business model. In addition, franchisees benefit from the use of established branding and receive support from the franchisor. Research design, data, and methodology: This study used the Preferred Reporting Items Systematics Review and Meta- Analyses (PRISMA) method to analyse data from 2003 to 2023 in the Web of Science and Scopus databases. Results: A total of 79 articles were identified and analysed to see trends and related themes such as product distribution, business distribution, business strategy, emerging market, and franchising relationship. Also, publication trends by year related to franchises are also presented. Conclusions: Overall, the research trend related to franchising as a global distribution is well seen, and every year, many researchers begin to explore the topic of franchising as a method of distribution that can be explored from various aspects either quantitatively or qualitatively. Lastly, limitations and recommendations are made to provide guidance for future studies related to the topic broadly and deeply in enriching the findings.